2020
DOI: 10.1097/md.0000000000018684
|View full text |Cite
|
Sign up to set email alerts
|

Association between changes in QRS width and echocardiographic responses to cardiac resynchronization therapy

Abstract: Background: Numerous studies have illustrated the association of QRS width with the incidence of echocardiographic response to cardiac resynchronization therapy (CRT). This study aimed to summarize the observational studies regarding the magnitude of change in QRS width between responders and nonresponders to CRT. Methods: The PubMed, Embase, and the Cochrane Library were systematically searched for relevant studies investigating the changes of QRS widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Prior studies have shown that reduction in QRS width is predictive of response to CRT with a prior meta-analysis showing a mean QRS reduction of 20.5 ms greater in responders versus nonresponders. [37][38][39][40] Within our cohort, there was not as significant a reduction, potentially secondary to many with an intrinsically paced rhythm before CRT upgrade.…”
Section: Discussionmentioning
confidence: 68%
“…Prior studies have shown that reduction in QRS width is predictive of response to CRT with a prior meta-analysis showing a mean QRS reduction of 20.5 ms greater in responders versus nonresponders. [37][38][39][40] Within our cohort, there was not as significant a reduction, potentially secondary to many with an intrinsically paced rhythm before CRT upgrade.…”
Section: Discussionmentioning
confidence: 68%
“…This is further supported by a recent meta-analysis of 11 (five prospective and six retrospective) studies, investigating the changes of QRS width with the incidence of echocardiographic response to CRT in 1524 patients, in whom QRS narrowing was significantly greater in responders than non-responders (weighted mean difference: −20.54 ms; p < .001). 36 By monitoring QRS duration, one can easily detect loss of capture in one ventricle with effectual capture in the other ventricle, as this will cause a change in the paced QRS morphology and duration (widening) in the 12-lead ECG similar to that of either single chamber RV or LV pacing (Table 3). Of course, complete loss of capture in both ventricles will expose the preprocedural baseline ECG morphology.…”
Section: Qrs Durationmentioning
confidence: 99%
“…8 ). The narrowing of the QRS complex after the biventricular pacing is associated with clinical and echocardiographic improvement [ 37 , 38 ]. This demonstrates the prognostic significance attributed to the ECG in patients with these devices.…”
Section: Surface Ecg In Patients With Cardiac Implantable Electronic ...mentioning
confidence: 99%